Determinations of dinotefuran and metabolite levels before and after household coffee processing in coffee beans using solid‐phase extraction coupled with liquid chromatography‐tandem mass spectrometry. (4th October 2018) - Chen, Zhaojie; Song, Shiming; Mao, Lianying; Wei, Jie; Li, Yuanfu; Tan, Huihua; Li, Xuesheng
Abstract: BACKGROUND: Coffee is one of the most popular beverages in the world. However, as daily consumables, coffee beans may contain pesticide residues that are capable of causing adverse health effects. Thus, we investigated residue dynamics in coffee beans using supervised field trials under Good Agricultural Practice conditions and determined the effects of household coffee processing on the coffee‐bean pesticide residues dinotefuran and its metabolites 1‐methyl‐3‐(tetrahydro‐3‐furylmethyl) urea (UF) and 1‐methyl‐3‐(tetrahydro‐3‐furylmethyl) guanidine (DN). RESULTS: The recovery rate of dinotefuran and its metabolites UF and DN was in the range 73.5%–106.3%, with a relative SD < 10%. The limits of detection and limits of quantification for dinotefuran, UF and DN were all 0.003 and 0.01 mg kg −1, respectively. Dissipation experiments were conducted over 2015 and 2016 and showed a mean half‐life of 40.8 days. Coffee processing procedures were performed as described for traditional household coffee processing in Ethiopia. Dinotefuran contents were reduced by 44.4%–86.7% with washing of coffee beans and the roasting process reduced these contents by 62.2%–100%. DN residues were not detected in roasted coffee beans before day 21 or in brewed coffee before day 35 and UF residues were not detected in brewed coffee before day 35. Kruskal–Wallis analyses indicated large variations in the stability of pesticide residues between processing methods ( P ≤ 0.05). Reductions of pesticide concentrations with washing were also significantly lower than those following roasting ( P = 0.0001) and brewing processes ( P = 0.002). Moreover, processing factors were less than one for all processing stages, indicating reductions of pesticides contents for all processing stages. CONCLUSION: The cumulative effects of the three processing methods are of paramount importance with respect to an evaluation of the risks associated with the ingestion of pesticide residues, particularly those in coffee beans. © 2018 Society of Chemical Industry